2006
DOI: 10.1128/jb.00486-06
|View full text |Cite
|
Sign up to set email alerts
|

The Nitric Oxide-Responsive Regulator NsrR Controls ResDE-Dependent Gene Expression

Abstract: The ResD-ResE signal transduction system is essential for aerobic and anaerobic respiration in Bacillus subtilis. ResDE-dependent gene expression is induced by oxygen limitation, but full induction under anaerobic conditions requires nitrite or nitric oxide (NO). Here we report that NsrR (formerly YhdE) is responsible for the NO-dependent up-regulation of the ResDE regulon. The null mutation of nsrR led to aerobic derepression of hmp (flavohemoglobin gene) partly in a ResDE-independent manner. In addition to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
103
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 40 publications
7
103
1
Order By: Relevance
“…During the course of this work, Nakano et al identified B. subtilis NsrR as a negative regulator of hmp and nasDEF by using lacZ fusion experiments (24). However, in contradiction to our data, it was suggested that an nsrR mutation does not cause derepression of nasD under aerobic conditions.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…During the course of this work, Nakano et al identified B. subtilis NsrR as a negative regulator of hmp and nasDEF by using lacZ fusion experiments (24). However, in contradiction to our data, it was suggested that an nsrR mutation does not cause derepression of nasD under aerobic conditions.…”
Section: Resultscontrasting
confidence: 54%
“…Nakano et al (24) suggested that it is NO and not nitrite that is sensed by NsrR, and this has also been implied for NsrR in Neisseria gonorrhoeae (28). However, in N. europaea (1,2), it has been suggested that nitrite, not NO, controls the activity of NsrR.…”
Section: Resultsmentioning
confidence: 99%
“…However, the iron may also be required for full activity of NssR, which is triggered by exposure to NO, GSNO, or related species. The nature of the sensing mechanism has not been elucidated, but in NO-sensing proteins, there are precedents for important roles for iron in Fe-S clusters (5,80,81), a mononuclear non-heme iron center (82), and heme (83)(84)(85). Because NssR is a positive regulator of cgb and the other NssR regulon genes, we suggest that there might exist an iron requirement either for interaction of NO with NssR or for reconstitution of NssR after interaction with NO.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of hmp transcription is complex involving several regulators including Fnr [12] and MetR [13]. Recently, it was discovered that the regulator NsrR represses hmp transcription in the absence of NO or nitrite [14,15]. NsrR is proposed to contain a NO-labile [Fe-S] cluster responsible for the NO-sensing capacity [14].…”
mentioning
confidence: 99%